IMPLEMENTING THE PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE STUDENTS' READING AND WRITING SKILLS IN NARRATIVE TEXT LEARNING FOR GRADE IV AT SDN 2 JULI - Fitriana; Rambang Muharramsyah; Alfi Syahrin (World Psychology, 2026)
This study aims to improve students’ reading and writing skills through the implementation of the Problem-Based Learning (PBL) model. The background of this research is based on the low level of students’ reading and writing skills, which are indicated by students’ lack of active participation in learning activities, difficulties in understanding reading texts, and limited ability to express ideas and thoughts in written form. This research employed a Classroom Action Research (CAR) design conducted in two cycles. The research subjects consisted of 32 students. Each cycle included the stages of planning, action implementation, observation, and reflection. Data were collected through observations of teacher and student activities, students’ worksheets (LKPD), and tests of reading and writing skills. The data were analyzed using descriptive quantitative and qualitative techniques. The results of the study indicate that the implementation of the Problem-Based Learning (PBL) model led to a significant improvement in students’ reading and writing skills. In the first meeting, only 10 students (31.25%) showed improvement in reading and writing skills. In the second meeting, the number of students who showed improvement increased to 15 students (46.88%). Furthermore, in the third meeting (Cycle II), the improvement became more significant, with 24 students (75%) demonstrating improved reading and writing skills. In addition, students’ learning activities and the quality of teaching practices also improved in each cycle. Based on these findings, it can be concluded that the Problem-Based Learning (PBL) model is effective in improving students’ reading and writing skills. This learning model enhances students’ active participation, critical thinking skills, and accuracy in reading and writing activities.